2016
DOI: 10.4196/kjpp.2016.20.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Minimal systems analysis of mitochondria-dependent apoptosis induced by cisplatin

Abstract: Recently, it was reported that the role of mitochondria-reactive oxygen species (ROS) generating pathway in cisplatin-induced apoptosis is remarkable. Since a variety of molecules are involved in the pathway, a comprehensive approach to delineate the biological interactions of the molecules is required. However, quantitative modeling of the mitochondria-ROS generating pathway based on experiment and systemic analysis using the model have not been attempted so far. Thus, we conducted experiments to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Individuals with cancers requiring irradiation of the base of the skull or brain are particularly vulnerable to cisplatin-induced ototoxicity [6], although the underlying molecular mechanism of cisplatin-induced ototoxicity is not fully understood. The generation of excessive ROS is considered to be one of the causative pathogenesis of cisplatin-induced ototoxicity [7]. In the antioxidant model, excessive ROS formation within the cochlea leads to a reduction in antioxidant enzymes following exposure to cisplatin chemotherapy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with cancers requiring irradiation of the base of the skull or brain are particularly vulnerable to cisplatin-induced ototoxicity [6], although the underlying molecular mechanism of cisplatin-induced ototoxicity is not fully understood. The generation of excessive ROS is considered to be one of the causative pathogenesis of cisplatin-induced ototoxicity [7]. In the antioxidant model, excessive ROS formation within the cochlea leads to a reduction in antioxidant enzymes following exposure to cisplatin chemotherapy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss can significantly hinder a patient’s quality of life, especially influencing social development such as language learning and speech in pediatric patients 5 . Although the underlying molecular mechanisms by which cisplatin causes ototoxicity is not fully understood, previous studies have demonstrated that cisplatin activates the death receptor pathway, endoplasmic reticulum-stress pathway, and mitochondrial reactive oxygen species (ROS)-generating pathway in normal cells, eventually leading to cell death 6 8 . The generation of excessive ROS is considered to be the major cause of cisplatin-induced ototoxicity, as well as the direct attack of cisplatin against DNA 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor effect of cisplatin is fundamentally exerted through cross-linking mitochondrial DNA, to form non-functional adducts, causing transcription blockage and impaired synthesis of many electron transport chain (ETC) components. Subsequently, reactive oxygen species (ROS) build up to provoke a state of mitochondrial oxidative stress, leading to the release of CYC to the cytosol to activate the caspases accomplishing apoptotic death [4], [26]. The phototoxic effect of PBM was explained by Karu [27], who reported that LLLI brings about an overall shift in the intracellular redox status and tilts the balance toward greater oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is a potent and widely used chemotherapeutic agent, being one of the first-line therapies for HNC [2]. Anticancer action of cisplatin is primarily mediated through induction of mitochondrial oxidative stress, leading to p53-dependent upregulation of proapoptotic Bax/Bak proteins, which allow for the exodus of cytochrome c (CYC) to the cytosol to further activate the executioner caspases 3, 6, and 7 of apoptotic death [3], [4]. Photobiomodulation (PBM) is a therapeutic approach that involves the use of LLL light in the visible red (600-700 nm) or near-infrared (NIR) (780-1000 nm) spectrum, to induce biological alterations in the irradiated cells, through induction of a nonthermal photochemical reaction [5].…”
Section: Introductionmentioning
confidence: 99%